Шпиндельные узлы агрегатных станков: альбом - Вороничев Н. М. Николай Максимович; Плашей Г. И. Григорий Ильич; Гиндин С. С. Самуил Соломонович; Лобусев В. М.; Марголин Н. У.; Марков В. М.; Френкель А. Я. (Москва, Машиностроение, 1983)
Авт. указаны на обороте тит. л.